Comparison of monotonic axial compressive behavior of rectangular concrete confined by FRP with different rupture strains. (13th September 2021) - Wang, Yanlei; Liu, Pu; Cao, Qi; Chen, Guipeng; Wan, Baolin; Wei, Zitao; Bai, Yu-Lei
Highlights: Behavior of rectangular concrete confined by CFRP, GFRP and PET FRP is compared. FRP confinement stiffness on behavior of FRP-confined concrete is studied. Effect of aspect ratio on behavior of FRP-confined concrete is studied. Abstract: Axial compressive behavior of rectangular concrete might differ greatly when it is confined by fiber reinforced polymer (FRP) with different rupture strains. To address this issue, this study experimentally investigated and compared the monotonic axial compressive behavior of rectangular concrete confined by FRP with three rupture strains. Axial compression experiments of 28 rectangular concrete stub columns confined by FRP were carried out. The FRP utilized in this study included conventional FRP with small rupture strain, i.e., carbon FRP (CFRP) and glass FRP (GFRP), and large rupture strain FRP (LRS-FRP), i.e., polyethylene terephthalate (PET) FRP. The key test parameters were the rupture strain of FRP, the FRP thickness, and the cross-sectional aspect ratio. Failure modes, stress vs. strain behavior, axial stress and strain relationship, hoop rupture strain, the effect of FRP confinement stiffness ratio, and the effect of cross-sectional aspect ratio were analyzed, respectively. Results of this research showed that the rupture strain of FRP exhibited significant influence on the failure mode and the axial deformation of rectangular concrete confined by FRP. FRP strain reduction factors were decreased with the increasing rupture strains of FRP. This is because the rectangular concrete confined by FRP with larger rupture strains dilated more non-uniformly than its counterpart using smaller rupture strain FRP. In addition, based on the transition point and the ultimate condition, the axial stress vs. strain curves of rectangular concrete confined by FRP could be categorized into three types, including sufficient, moderate, and insufficient FRP confinement, respectively.